Mechanistic Details of the Membrane Perforation and Passive Translocation of TAT Peptides. Issue 1 (30th October 2014) - Piantavigna, Stefania; Abdelhamid, Muhammad E.; Zhao, Chuan; Qu, Xiaohu; McCubbin, George A.; Graham, Bim; Spiccia, Leone; O'Mullane, Anthony P.; Martin, Lisandra L.
Abstract: The trans‐activator of transcription (TAT) peptide is regarded as the "gold standard" for cell‐penetrating peptides, capable of traversing a mammalian membrane passively into the cytosolic space. This characteristic has been exploited through conjugation of TAT for applications such as drug delivery. However, the process by which TAT achieves membrane penetration remains ambiguous and unresolved. Mechanistic details of TAT peptide action are revealed herein by using three complementary methods: quartz crystal microbalance with dissipation (QCM‐D), scanning electrochemical microscopy (SECM) and atomic force microscopy (AFM). When combined, these three scales of measurement define that the membrane uptake of the TAT peptide is by trans‐membrane insertion using a "worm‐hole" pore that leads to ion permeability across the membrane layer. AFM data provided nanometre‐scale visualisation of TAT punctuation using a mammalian‐mimetic membrane bilayer. The TAT peptide does not show the same specificity towards a bacterial mimetic membrane and QCM‐D and SECM showed that the TAT peptide demonstrates a disruptive action towards these membranes. This investigation supports the energy‐independent uptake of the cationic TAT peptide and provides empirical data that clarify the mechanism by which the TAT peptide achieves its membrane activity. The novel use of these three biophysical techniques provides valuable insight into the mechanism for TAT peptide translocation, which is essential for improvements in the cellular delivery of TAT‐conjugated cargoes including therapeutic agents required to target specific intracellular locations. Abstract : The worm turns : How does the TAT peptide translocate across a mammalian cell membrane? Three biophysical methods, which can spatially resolve scales from millimeter (quartz crystal microbalance with dissipation (QCM‐D)) and micrometer (scanning electrochemical microscopy (SECM)) to nanometer (AFM), provide evidence for wormhole‐like pores (see figure). The SECM image shows that these pores allow redox mediators to pass through to the sensor, but TAT disrupts bacterial‐mimetic membranes.